Influence of Atmospheric Turbulence Channel on a Super-Resolution Ghost Imaging Transmission System Based on Plasmonic Structure Illumination Microscopy - Wang, Kaimin; Wang, Zhaorui; Bai, Chunyan; Zhang, Leihong; Dai, Bo; Zhang, Yuxing; Ye, Hualong; Zhang, Zhisheng; Han, Xiaoxuan; Xue, Tong; Xu, Meiyong; Hu, Jiafeng; et al. (Frontiers in Physics, 2020)
Ghost imaging is a novel imaging technique that has various advantages over traditional imaging. However, most of the existing works on this technique do not achieve a better resolution than the diffraction limit. In this work, we presented a ghost imaging system with plasmonic structure illumination microscopy that achieved super-resolution imaging. The resolution reaches three to four times of the diffraction limit with surface plasmon polaritons and structure illumination microscopy theory. Since it can produce super-resolution images, this method has important implications in medical fields, such as in microimaging and endoscopy. We used the gamma–gamma intensity-fluctuation model to simulate the ghost imaging system in an atmospheric turbulence channel. By setting proper values of the transmission distance and refractive-index structure parameter, we obtain the peak signal-to-noise ratio (PSNR) performance and symbol-error rate (SER) performance. Finally, the PSNR and SER are used to evaluate the imaging quality, which provides a theoretical model to research the ghost-imaging algorithm further.